1993
DOI: 10.1021/bi00082a003
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization of fast and slow oxidized cytochrome c oxidase

Abstract: Oxidized cytochrome c oxidase can now be prepared either to react rapidly (fast) or to react slowly (slow) with cyanide [Baker, G.M., Noguchi, M., & Palmer, G. (1987) J. Biol. Chem. 262, 595-604]. Slow oxidized cytochrome c oxidase is also characterized by an integer spin g = 12 EPR signal which is absent in the fast form. The saturation magnetization of two samples of both forms of cytochrome oxidase has been studied at four applied magnetic fields (0.3125, 1.25, 2.5, and 5.0 T) over a temperature range from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 24 publications
4
38
1
Order By: Relevance
“…This issue has not been resolved, but we note that in resting CcO, the heme a 3 is high-spin (S = 5/2) based on 1) the λ max of the heme Soret band in the absorption spectrum of resting CcO that appears at 424 nm, indicative of a high-spin electronic structure, 1077,1078 2) SQUID magnetization studies that have demonstrated that the heme a 3 —Cu B pair is antiferromagnetically coupled to yield an overall S = 2 spin system, 1079,1080 and 3) EPR and MCD on resting ubiquinol oxidase that further indicates a small, anisotropic superexchange parameter ( J ≈ 1 cm −1 ) and a large positive zero-field splitting ( D = 5 cm −1 ) for heme a 3 . 1081 These spectroscopic observations are contradictory to those for the heme-peroxo-copper model complex, wherein the analogous end-on bridging peroxide causes the heme to be LS.…”
Section: Copper Active Sites That Activate Dioxygenmentioning
confidence: 95%
“…This issue has not been resolved, but we note that in resting CcO, the heme a 3 is high-spin (S = 5/2) based on 1) the λ max of the heme Soret band in the absorption spectrum of resting CcO that appears at 424 nm, indicative of a high-spin electronic structure, 1077,1078 2) SQUID magnetization studies that have demonstrated that the heme a 3 —Cu B pair is antiferromagnetically coupled to yield an overall S = 2 spin system, 1079,1080 and 3) EPR and MCD on resting ubiquinol oxidase that further indicates a small, anisotropic superexchange parameter ( J ≈ 1 cm −1 ) and a large positive zero-field splitting ( D = 5 cm −1 ) for heme a 3 . 1081 These spectroscopic observations are contradictory to those for the heme-peroxo-copper model complex, wherein the analogous end-on bridging peroxide causes the heme to be LS.…”
Section: Copper Active Sites That Activate Dioxygenmentioning
confidence: 95%
“…While this site is undoubtedly involved in consumption of the 'scalar' protons required for generation of the product water, it is extremely difficult to envisage it simultaneously involved in 'vectorial' proton translocation by a ligand exchange mechanism. However, in the case of derivatives like the fully oxidized resting and pulsed enzyme where heme a3 is magnetically coupled to CuB [29], presumably through bridging ligands, it is conceivable that ligand exchange processes at CuB might manifest themselves as perturbations in the spectral characteristics of heme as. Thus, by a process of elimination, the present data suggest CUB to be the site of the proton pump.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous spectroscopic studies have shown that the heme-copper site in HCO is spin-coupled in its Fe III -Cu B II resting state, suggesting that a ligand bridges the heme iron and copper 31,8487. The X-ray crystals of HCO from Paracoccus denitrificans 15 and bovine heart37 show electron density between the two metal centers, providing evidence to support a bridging ligand.…”
Section: Insights Into Chloride Binding To the Cub Center In Hcomentioning
confidence: 97%